Co-activation of synovial fibroblasts by laminin-111 and transforming growth factor-β induces expression of matrix metalloproteinases 3 and 10 independently of nuclear factor-κB. Issue 4 (24th August 2007) - Warstat, K; Pap, T; Klein, G; Gay, S; Aicher, W K
Abstract : We showed previously that the attachment of synovial fibroblasts to laminin (LM)-111 in the presence of transforming growth factor-β induces significant expression of the matrix metalloproteinase (MMP)-3. Here we go on to investigate the regulation of additional MMPs and their specific tissue inhibitors of matrix proteases (TIMPs). Changes in steady-state mRNA levels encoding TIMPs and MMPs were investigated by quantitative reverse transcription–polymerase chain reaction. Production of MMPs was monitored by a multiplexed immunoarray. Signal transduction pathways were studied by immunoblotting. Attachment of synovial fibroblasts to LM-111 in the presence of transforming growth factor-β induced significant increases in MMP-3 mRNA (12.35-fold, p<0.001) and protein (mean 62 ng/ml, sixfold, p<0.008) and in expression of MMP-10 mRNA (11.68-fold, p<0.05) and protein (54 ng/ml, 20-fold, p⩾0.02). All other TIMPs and MMPs investigated failed to show this LM-111-facilitated transforming growth factor-β response. No phosphorylation of nuclear factor-κB was observed. We conclude that co-stimulation of synovial fibroblasts by LM-111 together with transforming growth factor-β suffices to induce significant expression of MMP-3 and MMP-10 by synovial fibroblasts and that this induction is independent of nuclear factor-κB phosphorylation.